Prinsip Itqān Raqmī Dalam Kaidah “Man Ista‘Jala Qabla Awānihi ‘Uqiba Bi Ḥirmānih” Pada Digitalisasi Islam - Liddinillah, Muhammad Yakhsyallah; Sucipto, Imam (Sharia Journal and Education Center Publishing, 2025)
The advancement of digital technology has significantly transformed how Muslims access, study, and disseminate Islamic knowledge. This transformation requires an ethical and epistemological framework to ensure that digitalization processes remain grounded in Islamic values. This study aims to address three main research questions: how Islamic digitalization is understood within the context of Islamic scholarship and civilization; how the legal maxim “Man ista‘jala qabla awānihi ‘uqiba bi ḥirmānih” (Whoever rushes before its time will be deprived of it) relates to the phenomenon of digital acceleration; and how the principle of Itqān Raqmī (Digital Perfection) can serve as a moral and academic foundation for developing an ethical and civilized Islamic digitalization. Employing a qualitative library research method, this study uses descriptive and hermeneutic analyses of both classical and contemporary Islamic literature, including works by al-Suyūṭī and al-Syāṭibī, as well as modern academic discussions on digital ethics and Islamic epistemology. The findings reveal that Islamic digitalization is not merely a technical process but an epistemological transformation that requires patience, precision, and scholarly responsibility. The maxim “Man ista‘jala qabla awānihi ‘uqiba bi ḥirmānih” provides a moral warning against hasty adoption of technology without proper validation and adab, while the principle of Itqān Raqmī promotes a paradigm of digital excellence emphasizing accuracy, professionalism, and barakah (divine blessing) in every process of digitalization. Therefore, integrating the values of patience and digital perfection forms the ethical foundation for realizing an Islamic digitalization that is scholarly, ethical, and civilizational. Keywords: Islamic Digitalization; Man Ista‘jala Qabla Awānihi ‘Uqiba Bi Ḥirmānih; Itqān Raqmī; Islamic Digital Ethics.